Analysis of the Impact of Reservoir Development on the Availability of Water for Paddy Farming in Sanjai Village, East Sinjai District, Sinjai Regency - La Sumange; Jamal Jamal (Journal of Global Innovations in Agricultural Sciences)
Water supply which is a resource that must be sufficient in paddy farming. Reservoirs are civil construction buildings in the field of hydrology that are used to hold water so that it does not go straight to the sea, so that it can be used to improve the availability of water supply to paddy fields that cannot be reached by technical irrigation. The purpose of this study was to differentiating between the effects on water availability, farmer productivity, and economic impacts of the construction of the reservoir on the community. This study was conducted in Sanjai Village, East Sinjai District, Sinjai Regency. A total of 55 respondents of this study were farmers whose paddy fields used water from the reservoir and planted paddy as the main commodity of their farming. The method used to analyse the data was descriptive analysis and paired sample mean different test. The results of the study showed that the effect of reservoirs on water availability in addition to increasing farmer productivity can also reduce the risk of agricultural business due to drought and increase opportunities for farming, especially during the dry season. In addition, the construction of the reservoir has affected the availability of water in Sanjai Village, which was experienced by farmers after the construction of the reservoir, as well as a decrease in the intensity of floods and droughts, the smooth supply of water for the needs of farmers in farming in paddy fields so that the availability of water for farming in paddy fields is more sufficient after the construction of the reservoir and the impact after the development of the reservoir, from an economic point of view, the community was increasing production and productivity. It can be concluded that the construction of the reservoir has been achieved and the function of the reservoir for farmers was very useful and can also change cropping patterns as well as improve crop cultivation.